Cervical lymphadenopathy- a clinicopathological study of 50 cases in a tertiary level Hospital - Hossain, Md Zakir; Rafiquzzaman, Md; Hossain, Md Delwar; Azad, Muhammad Ali; Islam, Md Sirajul (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Cervical lymphadenopathy is common in Bangladesh and may present as diagnostic problem to the head neck surgeons. Diseases affecting cervical lymph nodes are of varying severity starting from simple curable infection to difficult incurable malignant disease. Objective: The purpose of this study was to observe the various clinical presentations of cervical lymphadenopathy and correlate histopathological findings with the clinical diagnosis. Methods: A cross sectional study was conducted during the period of 1st January 2013 to 31st December 2013 in CMH, Dhaka on 50 patients irrespective of age and sex presenting with cervical lymphadenopathy persisting for >2 weeks. Result: In this series, tissue diagnosis by biopsy found tuberculosis (TB) 38% cases, metastatic carcinoma in 26%, non-specific reactive hyperplasia in 22% and lymphoma in 14% cases. Sixty eight percent cases were below 40 years of age. Male to female ratio in this series was 2.12: 1. Conclusion: Twenty Four (48%) cases were diagnosed clinically as tubercular lymphadenitis, 12(24%) as metastatic carcinoma, 09(18%) non-specific reactive hyperplasia and 05(10%) cases were of lymphoma which were nearly similar to histopathological diagnosis. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22925 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014